Xenotransplantation: A New Era - Carrier, Amber N.; Verma, Anjali; Mohiuddin, Muhammad; Pascual, Manuel; Muller, Yannick D.; Longchamp, Alban; Bhati, Chandra; Buhler, Leo H.; Maluf, Daniel G.; Meier, Raphael P. H. (Frontiers in Immunology, 2022)
Organ allotransplantation has now reached an impassable ceiling inherent to the limited supply of human donor organs. In the United States, there are currently over 100,000 individuals on the national transplant waiting list awaiting a kidney, heart, and/or liver transplant. This is in contrast with only a fraction of them receiving a living or deceased donor allograft. Given the morbidity, mortality, costs, or absence of supportive treatments, xenotransplant has the potential to address the critical shortage in organ grafts. Last decade research efforts focused on creation of donor organs from pigs with various genes edited out using CRISPR technologies and utilizing non-human primates for trial. Three groups in the United States have recently moved forward with trials in human subjects and obtained initial successful results with pig-to-human heart and kidney xenotransplantation. This review serves as a brief discussion of the recent progress in xenotransplantation research, particularly as it concerns utilization of porcine heart, renal, and liver xenografts in clinical practice.